2016
DOI: 10.5539/ibr.v9n12p165
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Innovation for Chinese Small and Medium-sized Enterprises: Case Study in Beijing

Abstract: Innovation has been regarded as one of important impetuses to gain competitive advantages and achieve sustainable development for small and medium-sized enterprises (SMEs) in the past thirty years. However, SMEs in China have currently confronted a lot of problems impairing their innovation performance. This study aims to identify the main challenges hindering successful innovation of Chinese SMEs. Based on the previous academic studies, there are five research variables are developed and evaluated: lack of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The following literature review provides an overview of some studies on adopting web-based cloud storage. One study by Alqahtani et al, (2019) analyzed the adoption of web-based cloud storage by small and medium-sized enterprises (SMEs) in Saudi Arabia. The study found that SMEs that adopted web-based cloud storage reported significant improvements in data management, security, and efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The following literature review provides an overview of some studies on adopting web-based cloud storage. One study by Alqahtani et al, (2019) analyzed the adoption of web-based cloud storage by small and medium-sized enterprises (SMEs) in Saudi Arabia. The study found that SMEs that adopted web-based cloud storage reported significant improvements in data management, security, and efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…As such they lack the incentives and capacities to innovate (Xie et al, 2013;Newman et al, 2015;Naradda Gamage et al, 2020). As a consequence, most small enterprises rely on importing rather than innovating technology (Wonglimpiyarat, 2015;Alqahtani, 2016;Chu & Tan, 2019). For these reasons and in the absence of supportive policy, it is difficult to release the innovation potential of small firms in China.…”
Section: Weakness In the Measurement Of Innovation In China And How I...mentioning
confidence: 99%